Effects of Alprazolam on the Follicular Development of Rat Ovaries - Mohammad Shadkhast; Saied Habibian; Maryam Azadmanesh (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2018)
Introduction: Alprazolam is a benzodiazepine with several applications due to its pharmacological effects. Alprazolam is mostly used in the treatment of anxiety disorders. Alprazolam affects the brain and many other organs. Due to the excessive use of this drug, especially by women, the present study aimed to investigate the effects of alprazolam on the growth and development of ovarian follicles in female rats. Methods: This applied research was conducted on 24 adult female rats in 2015. Animals were randomly divided into four groups of six. In the first group, alprazolam was administered orally for 16 consecutive days (2 mg/kg). In the second and third group, alprazolam was administered orally for 16 consecutive days at doses of 4 and 6 mg/kg. Rats in the control group received water with the same volume and mode of administration at the same time as the test animals. Results: Histomorphological studies revealed that high doses of alprazolam (4 and 6 mg/kg) significantly decreased the number of graafian follicles (P<0.05). However, the number of atretic follicles significantly increased in the test groups (P<0.05). Conclusion: According to the results, high doses of alprazolam affected the follicular development of rat ovaries and may have adverse effects on the fertility of female rats.